2012
DOI: 10.1049/iet-rsn.2012.0024
|View full text |Cite
|
Sign up to set email alerts
|

Dolphin-inspired sonar system and its performance

Abstract: The sonar of dolphins has developed over millions of years of evolution and has achieved excellent performance levels. Using the excellent performance of the dolphins sonar as an inspiration, bio-inspired wideband acoustic sensing methods for underwater target detection and tracking are being developed. In this study the authors explore what they expect to gain from such a wideband sonar. The systems wideband sensors are based on bottlenose dolphins sonar, covering a frequency band from around 30 to 150 kHz an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Providing interesting and practical examples can inspire students to apply ecology concepts in their daily lives and work. Technology is often inspired by natural phenomena such as the submarine sonar system developed from the dolphin sonar (Pailhas et al ., 2012) or sustainable energy sources modeled after the hummingbird-wing structure (Ahmed et al ., 2017). Introducing such examples can help students understand the behavior of living things and ecology values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing interesting and practical examples can inspire students to apply ecology concepts in their daily lives and work. Technology is often inspired by natural phenomena such as the submarine sonar system developed from the dolphin sonar (Pailhas et al ., 2012) or sustainable energy sources modeled after the hummingbird-wing structure (Ahmed et al ., 2017). Introducing such examples can help students understand the behavior of living things and ecology values.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, indepth interviews and trials with 21 selected students revealed that including external resources on printed learning materials was less efficient, as students had to write down one after another. Review of learning materials submarine sonar system developed from the dolphin sonar (Pailhas et al, 2012) or sustainable energy sources modeled after the hummingbird-wing structure (Ahmed et al, 2017).…”
Section: Effectiveness Of Providing Links To External Resourcesmentioning
confidence: 99%
“…161 Advances to this method are partially bioinspired through the observation of dolphins, which also use frequency-rich pulses to obtain information about the environment in order to navigate. 162,163 Using the bioinspired approach, WBS has been recently used to not only inspect the positioning of subsea pipelines, but also provide information on flow assurance (i.e. whether flow is being obstructed by a foreign body).…”
Section: Electrical Phenomenamentioning
confidence: 99%
“…Classification of underwater targets from the acoustic backscattered signals includes discrimination between target and non-target objects as well as the description of background clutter . There are a lot of components that complicate this procedure such as: non-repeatability and alteration of the target signature with aspect angles, ranging and grazing angle , challenging natural and man-made clutter (Pailhas et al, 2012), effects of latitude and longitude (Williams, Fakiris, 2014), highly variable and reverberant working environment (Pan et al, 2014;Zhou, Zhang, 2005), dependency on the water's temperature, the salinity, the depth (Aubry et al, 2012) and the lack of any preknowledge about the form and the geometry of the non-target (Chu, Stanto, 2010).…”
Section: Introductionmentioning
confidence: 99%